Artist-Author in Action and Reflection - Michael Croft (Phenomenology & Practice, 2022)
The question of conjoined artistic- and phenomenological research practice is explored through two realizations of a drawing-based practice, complemented with a language-based practice that includes transcriptions of a spoken monologue while and about drawing. Through adapting the sense that the monologue’s addressee is an apparently other person, and narrating this situation, the author expresses through the article that the experiential process of drawing is automatically phenomenological. In turn, the article is a presentation of how phenomenological reflection is implicit in the practice. The artist- referenced in the article is termed the artist-author, declared as such to the reader, and is thereafter suggested as split into an apparently more reflexively inclined artist and a more reflectively inclined author/interlocutor. The hypothesis that both artistic- and phenomenological research can manifest as a single practice is embedded in the article’s manner of presentation, the reader of which is almost in the same interlocutory position as the author-, of the artist-author, in being able to notice this. The article’s actual author, however, refers to himself as a homunculus, in effect the hyphen of artist-author, that enables him to detach sufficiently from what can be read and seen to format the article in such terms as enable the reader to critically reflect on its hypothesis. The role of the camera itself, considered as a metaphor for interaction between the reflexive event and its subsequent language-based reflection, is also acknowledged, especially in the context of the artist-’s referencing in the drawing and in his speech how the camera both aids and obfuscates the process, and linking this to theory. The transcript conveys spoken enunciation, especially through its grammatically formatted disfluency and extended pauses, and the author’s personal declaration and observation of himself – reminding the reader that the article’s content is after all about its narrator – is italicized.